2021
DOI: 10.3390/agronomy11112209
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Assimilation and Translocation Regulate Grain Yield Formation in Wheat Crops (Triticum aestivum L.) under Post-Flowering Waterlogging

Abstract: In a two-year field study, we quantified the impact of post-flowering soil waterlogging on carbon assimilation and grain yield formation in wheat crops. At anthesis, wheat cultivars YangMai 18 (YM18) and YanNong 19 (YN19) were waterlogged for different durations, i.e., 0 (W0), 3 (W3), 6 (W6) and 9 (W9) days using artificial structures. Changes in leaf physiology, carbon assimilation and biomass production were quantified at 0, 7, 14, and 21 days after anthesis under all treatments. Short-term (W3) waterlogging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Due to dehydration and poor photosynthesis caused by low-temperature stress, dry matter accumulation of aboveground organs and transportation to grains significantly decreased [6]. Ma et al [51] also found that stress reduced dry matter assimilation and translocation capacity in the post-flowering stages. As a vital element, phosphorus improved stress tolerance and nutrient transport capacity to grains in wheat [52].…”
Section: Discussionmentioning
confidence: 99%
“…Due to dehydration and poor photosynthesis caused by low-temperature stress, dry matter accumulation of aboveground organs and transportation to grains significantly decreased [6]. Ma et al [51] also found that stress reduced dry matter assimilation and translocation capacity in the post-flowering stages. As a vital element, phosphorus improved stress tolerance and nutrient transport capacity to grains in wheat [52].…”
Section: Discussionmentioning
confidence: 99%
“…linked growth inhibition in peanut ( Arachis hypogea L.) variety DH-86 with impaired photosynthetic pigments, antioxidative enzymes, and chlorophyll fluorescence under waterlogging. Earlier studies also linked poor photosynthesis performance with waterlogging sensitivity in crops such as cotton ( Najeeb et al., 2015 ), and common and durum wheat ( Cotrozzi et al., 2021 ; Ma et al., 2021 ). Ma et al.…”
mentioning
confidence: 99%